Surgical and Systemic Treatment of Hereditary Breast Cancer: A Mini-Review With a Focus on BRCA1 and BRCA2 Mutations - Pouptsis, Athanasios; Swafe, Leyla; Patwardhan, Maneesha; Stavraka, Chara (Frontiers in Oncology, 2020)
Hereditary breast cancer accounts for 5-10% of breast cancer cases. The majority of familial cases have been linked to germline mutations in BRCA1 and BRCA2 genes, though other high penetrance susceptibility genes have also been identified through genomic advances. Optimal surgical treatment for these patients, who are of a younger age, has several challenges as it usually involves aggressive therapeutic and risk reducing interventions. At the same time, the therapeutic armamentarium for BRCA1/2 mutation carriers apart from platinum salts has been enriched with the addition of poly-ADP ribose polymerase (PARP) inhibitors with promising outcomes. In this review we provide a succinct and comprehensive overview of the surgical and systemic treatment of patients with BRCA1/2 mutation related breast cancer and an update on the most recent systemic treatment advances.